The Contribution of International Tourism to Indonesia's Economic Development: A Price, Income Elasticity, and Sustainable Tourism Policy Perspective - Nugroho, Alih Aji; Candrawati, Cindy (Journal of Governance, 2025)
This study explores the role of international tourism in Indonesia's economic development, focusing on price and income elasticity. And to develop a good sustainable tourism policy, this study also analyzes the literature using a systematic literature review. Utilizing panel data from 2007 to 2019 across nine key visitor countries, the research examines the impacts of real GDP per capita, relative tourism prices, and trade openness on tourist arrivals and also analyzes the 7 articles about sustainable tourism. The findings reveal that real GDP per capita significantly influences tourism demand, particularly in intercontinental markets, while price sensitivity dominates in Asian markets. Indonesian tourism is classified as a normal good, with demand increasing as income rises. These results highlight the importance of tailored strategies to enhance Indonesia's competitiveness, including price-driven promotions for Asian tourists and premium destination development for intercontinental visitors. The study underscores the potential of tourism to foster Indonesia’s sustainable economic growth, reduce regional disparities, and strengthen global development partnerships. Tourism is not only for gaining economic development but also should be sustained to achieve the SDGs goals.Policy recommendations include investing in tourism infrastructure, diversifying offerings, and enhancing data-driven decision-making to position Indonesia as a leading global destination and also make sure the tourism development is still sustainable.